Effect of calcium and vitamin D supplementation on bone mineral accrual among HIV-infected Thai adolescents with low bone mineral density - Thanyawee Puthanakit; Orasri Wittawatmongkol; Voraporn Poomlek; Tavitiya Sudjaritruk; Chantaphat Brukesawan; Torsak Bunupuradah; Sirintip Sricharoenchai; Thongsuai Chuanjaroen; Wasana Prasitsuebsai; Kulkanya Chokephaibulkit (Elsevier, 2018)
Background: The benefits of calcium and vitamin D supplementation for low bone mass remains controversial. This study assessed the changes in bone mineral density (BMD) during periods without and with calcium and vitamin D supplementation among HIV-infected adolescents with low BMD.Method: Perinatally HIV-infected Thai adolescents aged 12-20 years were enrolled into Phase 1 (pre-supplementation) to evaluate longitudinal change of BMD. We provided education about appropriate dietary intake and exercise. Lumbar spine (L2-L4) BMD and vitamin D status (25-hydroxyvitamin D [25(OH)D]) were assessed at baseline and at 12-24 month intervals. Participants with a BMD Z-score≤−2 were enrolled into Phase 2 (supplementation) that provided calcium 600 mg plus cholecalciferol 200 IU twice daily for 6 months. BMD and 25(OH)D were re-assessed at the end of study.Results: Ninety-four participants were enrolled into the Phase 1. Median age (IQR) was 14.3 (13.0-15.5) years, with 67% at Tanner stage 3-5, 89% with a plasma HIV-1 RNA>50 copies/mL. During Phase 1 and a 22.7-month follow-up, median L2-L4 BMD Z-scores remained unchanged (−1.06 vs −1.08, P=0.08), but 25(OH)D levels increased (24.7 vs 26.7 ng/mL, P=0.01). Twenty-six (28%) adolescents had low BMD and were enrolled into Phase 2, with 24 (92%) completing follow-up. The median L2-L4 BMD Z-scores (−2.59 vs −1.70; P>0.001) and calcium level (9.3 vs 9.5 mg/dL, P=0.04) significantly improved. There was an increase in BMD Z-scores during the 6-months post-supplementation as compared to the 21-month pre-supplementation period (0.65 vs −0.50, P=0.03).Conclusion: HIV-infected adolescents with low BMD had improved bone health after calcium and vitamin D supplementation. A randomised controlled trial is warranted to confirm the benefits of these supplements.